A formação do gestor escolar: um retrato a partir das diretrizes e matriz curricular de cursos de pedagogia - Soares, Marinês Mendes (2020)
This research is linked to the Master's Program in Education, from the University Nove de Julho (PPGE/Uninove), specifically, to the Research Line Popular Education and Cultures (LIPEPCULT). The research project proposed for this master's degree concerns the way in which the training of school managers has taken place today, exclusively, in what are called Pedagogy courses. In this sense, its development was guided by some questions, namely: has the initial training of the school manager / director been adequate or sufficient for the exercise of his performance at school? Does it respond to the skill and competency requirements required to exercise this role? Has the training offered by Pedagogy courses guaranteed the development of basic requirements for the training of school managers? This research had as general objective to analyze the formation of the school manager in the Pedagogy courses. The objectives were: to understand the different concepts that permeate the role of the school manager, among them: general and school administration; school management and management; democratic and participatory; analyze the practice of the school manager in the dimensions: pedagogical management, administrative management and people management; examine curricular matrices of the Pedagogy course, offered by some public and private universities in the capital of the State of São Paulo. In this study, it was analyzed from a qualitative research, of bibliographic and documentary type, what the theoretical scholars of the area and the national guidelines indicate about the formation, responsibilities, competences and the role of the school manager regarding the demands that arise in the position of school principal / manager. The researches that deal with subjects related to the administration, school administration and democratic management gave support to the elaboration of this investigation and reinforced the quality and efficiency necessary to the education and as a consequence, they emphasized the importance of the existence of a participative democratic management inside the schools, aiming at an education that values the relationships that take place in the school context, in which the subjects are co-responsible in the participation of the investigative process of the difficulties that present themselves there. It was also evident that the Pedagogy course does not guarantee academic training for the exercise of the function of the school manager in its entirety, which can be justified by the recommendations explained in the current educational guidelines. With that, it was understood that there is much to be investigated and discussed with regard to the training of school managers.